Theoretical contrastation of procedimental, attitudinal and cognitive aspects in the teaching and learning of Statistics - Hernández Padilla, Lisceth del Carmen (2019)
In the research, concepts associated with the procedural, attitudinal and cognitive aspects in the teaching and learning of statistics of the Academic Program for Business Development were contrasted. The design of the investigation was documentary and field, of explanatory type. For the conceptual construction, the theoretical concepts (unobservable properties) included the definition of the procedural, attitudinal and cognitive. From there, the derivative concepts inherent to the theorists were generated through correspondence rules and by means of an empirical definition the derived concepts were related to the observables (metacodes). A theoretical network was designed. Through the concepts, foci of pedagogical intervention were detected in the immediate attention areas of the context under study.